Analysis of a Discrete Predator-Prey Model for Controlling The Extinction of The Pesut Mahakam (Orcaella brevirostris) with Toxic Effect at The Mahakam River (Jurnal Matematika, Statistika dan Komputasi, 2023)
The Pesut Mahakam (Orcaella brevirostris) is an East Kalimantan animal in critical condition and on the verge of extinction. One of the causes of the extinction of the Mahakam dolphins is the toxic effects of environmental pollution. In this study, an analysis of the discrete predator-prey model using Euler's forward difference between the Pesut Mahakam (Orcaella brevirostris) and its prey was investigated. Dynamic analysis includes determining the equilibrium point, stability analysis of the equilibrium point, and numerical simulation. The value of the Mahakam dolphin growth rate parameter (predator) is obtained by adjusting the curve based on data in the field. Numerical simulations were carried out to describe the results of the analysis. Changes in the value of the toxic effect rate parameter affects the number of Mahakam dolphins and their prey.
Keywords: Pesut Mahakam; numerical simulation; predator-prey model; stability analysis; toxic effect